The spontaneous immortalization probability of mammalian cell culture strains, as their proliferative capacity, correlates with species body mass, not longevity - Matteo Perillo; Angela Punzo; Cristiana Caliceti; Christian Sell; Antonello Lorenzini (Biomedical Journal, 2023)
Background: The Peto's paradox consists in the observation that individuals from long-lived and large animal species do not experience a higher cancer incidence, despite being exposed for longer time to the possibility of accumulating mutations and having more target cells exposed to the phenomenon. The existence of this paradox has been recently confirmed (Vincze et al., 2022). Concurrently, robust evidence has been published that longevity involves a convergent evolution of cellular mechanisms that prevent the accumulation of mutations (Cagan et al., 2022). It remains unclear which cellular mechanisms are critical to allow the evolution of a large body mass while keeping cancer at bay. Methods: Adding to existing data linking cellular replicative potential and species body mass (Lorenzini et al., 2005), we have grown a total of 84 skin fibroblast cell strains from 40 donors of 17 mammalian species and analyzed their Hayflick's limit, i.e., their senescent plateau, and eventual spontaneous immortalization escape. The correlation of immortalization and replicative capacity of the species with their longevity, body mass and metabolism has been assessed through phylogenetic multiple linear regression (MLR). Results: The immortalization probability is negatively related to species body mass. The new evaluation and additional data about replicative potential strengthen our previous observation, confirming that stable and extended proliferation is strongly correlated with the evolution of a large body mass rather than lifespan. Conclusion: The relation between immortalization and body mass suggests a need to evolve stringent mechanisms that control genetic stability during the evolution of a large body mass.